Two views of the lender of last resort: Thornton and Bagehot - David Laidler (The University of Western Ontario, Department of Economics, 2002)
Henry Thornton and Walter Bagehot were both advocates of discretionary monetary policy, especially as regards the Bank of England's role as a lender of last resort, but they differed on many details of the case. Where Bagehot thought that the Bank's central position in the financial system was purely the product of a specific monopoly privileges, Thornton also saw it as the desirable and natural outcome of the operations of banking; where Bagehot located the productivity of banking in credit markets, Thornton stressed the importance of liability side of the system's balance sheet; and where Bagehot took the desirability of gold convertibility for granted, Thornton was willing to trade off this goal against the maintenance of monetary stability.
Keywords: 330